2013
DOI: 10.1088/0022-3727/46/34/345306
|View full text |Cite
|
Sign up to set email alerts
|

High-vacuum synthesis of SiC from rice husk: a novel method

Abstract: A new technique for the production of SiC from rice husk is reported in this paper. The high-purity β-SiC is synthesized in a short time of 5 min. The samples are characterized by x-ray diffraction and scanning electron microscopy analysis. The results are compared with the previously reported result that was obtained by conventional process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In contrast, it was found that the pyrolysis in vacuum guaranteesthe lower pressure around the reactants and consequently increases the formation of SiC at temperature around 1550°C due to increment of intimate contact between SiO 2 and C. MoreoverRadhakrishna and Sanghi [179] reported that vacuum prevents whisker growth since it removes the vapors containing the whisker growth species.Sarangi et al [219]showed in high-vacuum at ~ 1400°C , high crystaline β-SiC particles of very fine sizeformed along with some amountof unreacted silica in less than 5 min. Fig.…”
Section: Effect Of Atmosphere On Sic Formationmentioning
confidence: 99%
“…In contrast, it was found that the pyrolysis in vacuum guaranteesthe lower pressure around the reactants and consequently increases the formation of SiC at temperature around 1550°C due to increment of intimate contact between SiO 2 and C. MoreoverRadhakrishna and Sanghi [179] reported that vacuum prevents whisker growth since it removes the vapors containing the whisker growth species.Sarangi et al [219]showed in high-vacuum at ~ 1400°C , high crystaline β-SiC particles of very fine sizeformed along with some amountof unreacted silica in less than 5 min. Fig.…”
Section: Effect Of Atmosphere On Sic Formationmentioning
confidence: 99%
“…Rice husk is still an environmental problem today, as not all waste generated is disposed of properly, especially in countries that produce large amounts of rice, such as China, India, and Brazil [4,16]. On the other hand, the silicon carbide production industry requires a source of high-purity silica and carbon.…”
Section: Neste Estudo a Casca De Arroz Foi Utilizada Para A Síntese mentioning
confidence: 99%
“…The benefit of using rice husk as a raw material is its low cost since in most cases the husk is considered a waste [15]; also SiC formation occurs at lower temperatures (1200 to 1500 °C) when compared to the reactions between solid quartz and graphite (1200 to 2000 °C); according to Eqs. A to C [16][17][18], this is due to the high surface area of the rice husk and the presence of an ionic mixture between silica and carbon in its composition.…”
Section: Introductionmentioning
confidence: 99%